2020
DOI: 10.1177/0363546520932923
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes and Survivorship of Fresh-Frozen Meniscal Allograft Transplant With Soft Tissue Fixation: Minimum 10-Year Follow-up Study

Abstract: Background: Meniscal allograft transplant (MAT) is considered an effective procedure for reducing pain and improving knee function. Nevertheless, the current knowledge regarding the results of MAT is limited to short- to mid-term follow-up studies, especially for arthroscopic techniques. Purpose: To evaluate the long-term clinical outcomes, reoperations, and failures with a minimum follow-up of 10 years af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 40 publications
2
36
1
Order By: Relevance
“…Of those, the articles with the greatest sample sizes [ 45 , 47 , 49 ] were included. Consequently, 44 articles were included in this review [ 8 , 10 , 32 , 34 , 36 , 42 , 45 , 47 , 49 , 51 85 ] and were assessed for methodological quality (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of those, the articles with the greatest sample sizes [ 45 , 47 , 49 ] were included. Consequently, 44 articles were included in this review [ 8 , 10 , 32 , 34 , 36 , 42 , 45 , 47 , 49 , 51 85 ] and were assessed for methodological quality (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, we pooled studies with different follow-ups (6 months to 20 years) in the analyses. Several studies show that the time from primary reconstruction to subsequent C-ACL injury is often 3–4 years [ 8 , 52 , 73 ], indicating that studies with a follow-up of less than 3 years may not be able to capture all C-ACL injuries and consequently the results from such studies should be interpreted with caution. Our sensitivity analysis also showed that lower age (as a continuous variable) was no longer a risk factor for C-ACL injury if studies with a follow-up of ≤ 2 years were excluded, whereas there were no differences in the result for other risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,20 Surgical meniscal allograft failure was defined as the need for subtotal or total meniscal allograft resection, meniscal allograft repair, revision MAT, or conversion to unicompartmental or total knee arthroplasty. 10 Central meniscal allograft tears were left in situ or treated via arthroscopic debridement (resection of no more than one-third of the allograft width) and were not considered a surgical meniscal allograft failure. Peripheral meniscal allograft tears that required partial resection (more than one-third of the allograft width) or total resection of the meniscal allograft were considered as surgical meniscal allograft failure.…”
Section: Indications Surgical Technique and Rehabilitationmentioning
confidence: 99%
“…In contrast, clinical meniscal allograft failure is defined as a postoperative Lysholm score \65 points. 10,21,37,44 Risk factors associated with surgical meniscal allograft failure include older patient age and presence of articular cartilage lesions at the time of MAT, lateral MAT, subsequent operative procedures, nonanatomic placement of the meniscal allograft root, and undersized meniscal allografts. 3,10,16,[20][21][22]37 Moreover, 1 study reported extensive meniscal allograft tears as the primary cause of surgical meniscal allograft failure, requiring subsequent graft removal.…”
mentioning
confidence: 99%